GAMBARAN KARAKTERISTIK HERPES ZOSTER DI POLIKLINIK KULIT DAN KELAMIN RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR PERIODE JANUARI 2011-DESEMBER 2013 - Ningrat, Dewa Ayu Agung Anggita; Darmada, I.G.K. (E-Jurnal Medika Udayana, 2017)
Herpes zoster is a disease that caused by varicella zoster virus (VZV), that results pain with blister coetaneous lesion following dermatome direction, as the clinical manifestations. This disease has high morbidity. Although the morbidity is high, there is not specific data about characteristic figure of herpes zoster in Bali in the last 5 years. A descriptive research was conducted to find out the characteristic figure of herpes zoster at Poliklinik Kulit dan Kelamin RSUP Sanglah, January 2011-December 2013. The prevalence of herpes zoster in 2011-2013 is 229 cases with 48% male and 52% female. Cases with age range <20 years old is 14%, 20-39 years old 16%, 40-59 years old 43%, and >59 years old 27%. The percentages of herpes zoster cases based on dermatome are; herpes zoster generalisata 2%, optalmicus 11%, fascialis 5%, servicalis 6%, torachalis 20%, and lumbosacralis 4%. The conclusion is characteristic figures of herpes zoster are different based on age, sex, and dermatome location. Keywords: Herpes Zoster, Prevalence, Dermatome